Distance, Transportation Cost, and Mode of Transport in the Utilization of Facility-Based Maternity Services: Evidence from Rural Bangladesh. (December 2014) - Keya, Kaji Tamanna; Rob, Ubaidur; Rahman, Md. Moshiur; Bajracharya, Ashish; Bellows, Benjamin
Although the maternal mortality ratio in Bangladesh has decreased, significant underutilization of facilities continues to be a persistent challenge to policy makers. Women face long distances and significant transportation cost to deliver at health facilities. This study identifies the distance traveled to utilize facilities, associated transportation cost, and transport mode used for maternal healthcare services. A total of 3, 300 mothers aged 18–49 years, who had given birth in the year before the survey, were interviewed from 22 sub-districts in 2010. Findings suggest that facility-based maternal healthcare service utilization was very poor. Only 53% of women received antenatal care, 20% used delivery care. and 10% used postnatal care from health centers. Median distance traveled for antenatal and postnatal check-ups was 2 kilometers but 4 kilometers for complication management care and delivery. Most women used non-motorized rickshaw or van to reach a health facility. On average, women spent Taka 100 (US1.40) as transportation cost for antenatal care, Taka 432 (US6.17) for delivery, and Taka 132 (US1.89) for postnatal check-up. For each additional kilometer, the cost increased by Taka 9 (US0.13) for antenatal, Taka 31 (US0.44) for delivery, and Taka 8 (US0.11) for postnatal care.